1996
DOI: 10.2337/diab.45.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Regenerating Gene Overexpression in the Nonobese Diabetic Mouse During Active Diabetogenesis

Abstract: The reg gene has previously been shown to be associated with regeneration of pancreatic islets. Strategies for influencing the replication and the growth of the (3-cell mass may be important for prevention and/or treatment of type I diabetes. In this study, we have examined the level of reg gene expression at various degrees of diabetogenesis in the pancreas of the NOD mouse (male, female, and cyclophosphamide-treated male) using both human reg cDNA as the probe and dot blot analysis. The expression of the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
2
18
1
Order By: Relevance
“…This data is in keeping with the results of McKie et al [14]who demonstrated by Northern blot that the steady-state level of PAP mRNA in the normal mouse pancreas was virtually undetectable. However, we found significantly higher levels of PAP mRNAs in the NOD mouse pancreas but in contrast to that we previously found for reg genes [7, 8]there were no differences between diabetes-prone female mice and diabetes-resistant male mice, demonstrating that the increase of PAP mRNA levels in NOD mice was not specifically associated with a high risk of diabetes. These results suggest that the PAP gene expression in this strain is only correlated with the presence of insulitis, the main characteristic of the NOD mice which corresponds to lymphocyte infiltration.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This data is in keeping with the results of McKie et al [14]who demonstrated by Northern blot that the steady-state level of PAP mRNA in the normal mouse pancreas was virtually undetectable. However, we found significantly higher levels of PAP mRNAs in the NOD mouse pancreas but in contrast to that we previously found for reg genes [7, 8]there were no differences between diabetes-prone female mice and diabetes-resistant male mice, demonstrating that the increase of PAP mRNA levels in NOD mice was not specifically associated with a high risk of diabetes. These results suggest that the PAP gene expression in this strain is only correlated with the presence of insulitis, the main characteristic of the NOD mice which corresponds to lymphocyte infiltration.…”
Section: Discussioncontrasting
confidence: 56%
“…We observed a pancreatic overexpression of the reg II gene (and to a lesser degree of the reg I gene) in female NOD mice which develop diabetes early in life, whereas NOD males, which are relatively protected, have a low mRNA level similar to the level found in a control mouse strain [7, 8]. The specificity of this overexpression in the diabetogenic process was reinforced by the fact that it was also observed in NOD male mice after treatment with cyclophosphamide, an immunosuppressive drug known to accelerate diabetes in this strain.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The intra- and inter-molecular crosslinks are believed to play a significant role in these changes in the extracellular matrix [8]. Pentosidine, a crosslink between arginine and lysine, is one of the AGEs [9].…”
Section: Introductionmentioning
confidence: 99%